Incidence of side effects of antituberculosis drugs and their related factors in northern Iran: a retrospective cohort study - Kheradmand, Motahareh; Afshari, Mahdi; Aarabi, Mohsen; Abedi, Siavosh; Parsaee, Mohammadreza; Nezammahalleh, Asghar; Moosazadeh, Mahmood (German Medical Science GMS Publishing House, 2024)
Background: Antituberculosis drugs may cause mild, moderate or severe adverse drug reactions (ADR) leading to poor compliance. Description of the pattern of ADR and their related factors can help tuberculosis (TB) control program as part of the WHO programs. This study aims to investigate the incidence of ADR and associated factors among TB patients in northern Iran. Methods: This is a retrospective cohort study. The required information, including year of diagnosis, age, gender, residence area, nationality, HIV co-morbidity, history of anti TB treatment and ADR, was obtained from the Deputy of Health, Mazandaran University of Medical Sciences, Iran. All data were analyzed using SPSS version 21 software. Results: Out of 3903 TB patients, 136 (3.5%) experienced major ADR. The incidence of ADR for men and women as well as for those with and without previous treatment history were 3.9% vs. 3.3% and 5.3% vs. 3.4%, respectively (p>0.05). Multiple logistic regression models showed a higher chance of ADR among those aged over 59 compared with those aged under 29 (OR=2.63, 95% confidence interval: 1.54-4.49). Conclusions: Age over 59 can be considered a risk factor for ADR with anti-TB drug administration.